Une analyse des qualités psychométriques du Level of Service/Case Management Inventory (LS/CMI) a partir de la theorie des réponses aux items - Giguère, Guy (Canadian journal of criminology and criminal justice, 2017)
Andrews, Bonta, and Wormith (2004) present the Level of Service/Case Management Inventory (LS/CMI) as a fourth generation risk/needs assessment tool for adult convicted offenders. Very limited research, however, has been conducted to verify Andrews et al.'s (2004) assertions about the validity of this tool. This study, therefore, provides a detailed analysis of the internal structure of the LS/CMI as well as its predictive validity. This study is based on data from a sample of 17,651 adult male offenders followed prospectively over a one-year period. Using item response theory analyses, the study findings indicate that in terms of predictive validity, the dynamic items of the assessment tool do not provide a significant improvement. In the end, after removal of several factors, mostly dynamic factors, it is shown that the static items alone prove as valid as those instruments of the third and fourth generation. As a result, the psychometric analyzes raise fundamental questions about the validity of the instrument but also its use and role with adult convicted offenders